Mass resection as a candidate treatment for uterine PEComas of uncertain malignant potential: a case report and literature review - Shi, Haijuan; Yin, Yan; Liang, Shoujun; Liu, Chuanzhong; Huang, Yibao; Lu, Bingfeng; Zhang, Liying (Frontiers in Oncology, 2025)
BackgroundPerivascular epithelioid cell tumours (PEComas) occurring in the uterus are rare, with surgery being the most recommended primary treatment for malignant cases. This study aims to provide clinical guidance on the clinicopathological features and appropriate treatment options for patients with uterine PEComas of uncertain malignant potential.CasesThis case series summarises the clinical courses of 13 patients diagnosed with uterine PEComas of uncertain malignant potential, including clinical and pathological data as well as their outcomes. We identified one case at our hospital, and data for the other 12 cases were extracted from the PubMed database. The 13 patients were aged 9–75 years, with tumour sizes ranging from 1 to 21 cm, and follow-up times ranging from 2 to 71 months. The most common signs and symptoms included abnormal uterine bleeding (AUB) and abdominal pain. Most of the patients (11/13) were managed surgically without any chemotherapy or radiation therapy. Except for the patients who were lost to follow-up, 11 patients were free of any recurrence or metastasis at their last follow-up. Patients with group A tumours (abundant HMB45 expression) had a longer disease-free survival than those with group B tumours.ConclusionsSurgery alone may be appropriate for uterine PEComas of uncertain malignant potential. Surgical treatment plans should consider the patient’s age, fertility requirements, and personal preferences. Mass resection is a viable treatment option for fertility preservation in reproductive-age patients.